Optimizing Subnational Warning Mechanisms: Community and Practitioner Perspectives on the 2018 Anak Krakatau-Induced Tsunami in Pandeglang, Indonesia - Wicaksono, Willy; Sopaheluwakan, Jan; Desportes, Isabelle (TDMRC, Universitas Syiah Kuala, 2023)
To help optimize tsunami warning system in Indonesia, particularly concerning non-seismically inducted tsunamis and at the subnational level, this study employs a qualitative methodology to draw lessons from the Anak Krakatau-induced tsunami on December 22, 2018. A total of 37 community members and 35 government officials in Pandeglang Regency and at the national level participated in in-depth interviews and focus groups discussions. Participants emphasized bureaucratic mismatches and delays, underlining the urgent need for clearer national-subnational communication. The study presents concrete and actionable recommendations for refining warning reception, decision-making, legitimization processes and warning dissemination. Proposed changes such as diversifying information sources and localizing tsunami siren control aim to empower local entities and expedite responses, overall increasing community preparedness for future tsunami threats. By contrasting the experiences and recommendations of affected communities, local government and national-level actors, the study makes a case for improving warning systems based on the past experience and recommendations of the first concerned and first impacted.